Managing pupil behaviour : improving the classroom atmosphere - Haydn, Terry, 1951- (Abingdon : Routledge, 2012)
'Managing Pupil Behaviour provides routes through the classroom management maze to help practising and aspiring teachers learn to manage behaviour effectively in their classrooms. Using Terry Haydn's unique 10-point scale, it encourages teachers to think about the degree to which they are relaxed and in assured control of their classrooms and can enjoy their teaching. Drawing on the views of over 140 teachers and 700 pupils, it provides insights into the factors which enable teachers to manage learning effectively in their classrooms, so that pupils can learn and achieve, and teachers can enjoy their work. Key issues explored include the factors that influence the working atmosphere in the classroom, the impact of that atmosphere on teaching and learning, and tensions around inclusive practice and situations where some pupils may be spoiling the learning of others. This new edition has been fully updated to take account of recent research and inspection findings and includes a new chapter exploring the wide range of sophisticated skills that expert teachers deploy in order to get pupils to want to learn, and to enable teachers to work in classrooms where the climate is perfect for learning. Managing Pupil Behaviour will help all teachers ensure'the right to learn' for all the pupils in their care and to think about different ways to approach this vitally important aspect of their working lives'--
The working atmosphere in the classroom and the right to learn -- Teachers' views about colleagues who are good at managing learning -- Planning for learning -- Managing learning in classrooms -- Understanding pupils -- Working in schools --'Complex and sophisticated skills...' -- Telling the truth about the working atmosphere in the classroom.
Includes bibliographical references : (p. 202-209) and index.
Keywords: Classroom environment; Behavior modification; Students -- Psychology